Synthesis, Crystal Structure and Bioactivity of Phenazine-1-carboxylic Acylhydrazone Derivatives - Shouting Wu; Xi Liang; Fang Luo; Hua Liu; Lingyi Shen; Xianjiong Yang; Yali Huang; Hong Xu; Ning Wu; Qilong Zhang; Carl Redshaw (Molecules, 2021)
A phenazine-1-carboxylic acid intermediate was synthesized from the reaction of aniline and 2-bromo-3-nitro-benzoic acid. It was then esterified and reacted with hydrazine hydrate to afford phenazine-1-carboxylic hydrazine. Finally, 10 new hydrazone compounds 3a–3j were obtained by the condensation reaction of phenazine-1-carboxylic acid hydrazide and the respective aldehyde-containing compound. The structures were characterized by 1H and 13C NMR spectroscopy, MS and single crystal X-ray diffraction. The antitumor activity of the target compounds in vitro (HeLa and A549) was determined by thiazolyl blue tetrazolium bromide. The results showed that compound (E)-N′-(2-hydroxy-4-(2-(piperidine-1-yl) ethoxy) benzyl) phenazine-1-carbonyl hydrazide 3d exhibited good cytotoxic activity.